The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00436-021-07179-8
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and biochemical abnormalities in hunting dogs infected with Acanthocheilonema reconditum, associated risk factors, and a European overview

Abstract: Acanthocheilonema reconditum is a filarial parasite transmitted by arthropods (fleas, lice, and ticks) that infect dogs. There is minimal published data available to date on potential haematological and biochemical changes associated with this parasitic infection. Study aims were (i) provide an overview of A. reconditum in Europe, (ii) define A. reconditum prevalence and risk factors in a specific dog population (hunting) from southern Italy, and (iii) assess the frequency of haemato-biochemical abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 85 publications
3
6
1
Order By: Relevance
“…Leukocytosis with eosinophilia has been reported in dogs with microfilaremia by A. reconditum [44,45], which agrees with the hematological alterations in the two dogs. According to Hashem and Badawy [44], lymphocytosis, which was found in P4, P8, and P10, could be related to a chronic phase of filariasis accompanied by normochromic normocytic anemia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Leukocytosis with eosinophilia has been reported in dogs with microfilaremia by A. reconditum [44,45], which agrees with the hematological alterations in the two dogs. According to Hashem and Badawy [44], lymphocytosis, which was found in P4, P8, and P10, could be related to a chronic phase of filariasis accompanied by normochromic normocytic anemia.…”
Section: Discussionsupporting
confidence: 81%
“…According to Hashem and Badawy [44], lymphocytosis, which was found in P4, P8, and P10, could be related to a chronic phase of filariasis accompanied by normochromic normocytic anemia. In addition, the increase in plasma proteins with leukocytosis, eosinophilia, and lymphocytosis may be related to the immune response of the dog to circulating Available at www.veterinaryworld.org/Vol.16/January-2023/11.pdf microfilarial antigens [44,45]. Thrombocytopenia observed in P2, P6, P7, P8, and P10 may be associated with other vector-borne diseases (Ehrlichia canis, Anaplasma phagocytophilum, or Anaplasma platys, and Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…immitis in biting-midges ( 10 ). In addition, Acanthocheilonema reconditum is a worldwide distributed flea-transmitted filarioid, which is considered as the most prevalent filaroid infesting dogs in the Mediterranean Basin ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Waiwai hunting dogs have previously been reported to receive more care from their owners and appear larger and healthier than non-hunting dogs [ 33 – 35 ]; thus, evidence of better health might be reflected by lower WBC, strongyle-type ova, and eosinophil counts. However, hunting dogs, both directly from their interactions with prey, and indirectly through their increased time spent in the forest [ 51 54 ], may have exposure to a greater diversity of parasites [ 55 ] or experience more trauma related to hunting activities, which may be reflected by higher WBC, strongyle-type ova, and eosinophil counts [ 56 ]. Previous studies at other sites have shown higher diversity and prevalence of parasites among hunting dogs compared to non-hunting but free roaming dogs [ 52 , 53 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies at other sites have shown higher diversity and prevalence of parasites among hunting dogs compared to non-hunting but free roaming dogs [ 52 , 53 , 56 , 57 ]. In addition, hunting dogs with higher parasitic loads have been shown to exhibit higher WBC and eosinophil counts [ 51 , 55 , 58 ]. Therefore, we hypothesized that hunting dogs would differ significantly from non-hunting dogs in WBC, strongyle-type ova, and eosinophil counts, but did not predict the direction of this relationship.…”
Section: Methodsmentioning
confidence: 99%